Introduction to Energy and Energy Saving Culture for ABA 25 Malang Kindergarten Students - Mamungkas, Mohamad Irkham; Subekti, Nur; Murjito, Murjito (Edumedia Solution, 2025)
This community service departs from the lack of basic understanding of ABA 25 Malang kindergarten students about the concept of energy and the importance of an energy-saving culture, a crucial issue given the challenges of the energy crisis and global climate change. To overcome this problem, we implemented a solution in the form of an interactive educational program designed specifically for early childhood. The methods used include storytelling, simulation games, educational songs, and hands-on practices (e.g. turning off lights when leaving the room or closing the water tap after use) that are presented in an interesting and digestible manner. The results of this community engagement activity showed a significant increase in students' awareness and understanding of various energy sources as well as the benefits of energy saving, as evidenced by the positive responses and simple behavioral changes that began to be demonstrated in daily activities at school. The conclusion of this service confirms that a fun and practical educational approach at an early age is very effective in instilling energy conservation values and building the foundation of environmental awareness for future generations.